PENGARUH KUALITAS PRODUK, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI MCDONALD’S SUKAHATI CIBINONG - Verry Cyasmoro; Fransischa Sri Rejeki (LPPM Universitas Asa Indonesia, 2017)
The purpose of this research is to determine the Quality of Product, Price, and Location against Purchasing Decision partially, and and simultaneously at Mc Donald’s Out let at Sukahati, Cibinong. The population of this research are the customers at the certain period of time, while the sample taken using Slovin formula. The total of respondents are 100 persons. The analysis method by multiple regression applying F-test, t-test and coorelation determination. Data were obtained by using SPSS versi 20. The results shows that quality of product, prioce, and location aremsignificant in partially, as well as simultaneously, at the 5% of degree of significance. It is then suggested to boost other method or marketing mix to maximize customers to that outlet at Sukahati, Cibinong.